Exercise improved bone health in aging mice: a role of SIRT1 in regulating autophagy and osteogenic differentiation of BMSCs - Zhu, Chengyu; Ding, Haili; Shi, Liang; Zhang, Shihua; Tong, Xiaoyang; Huang, Mei; Liu, Lifei; Guan, Xiaotian; Zou, Jun; Yuan, Yu; Chen, Xi (Frontiers in Endocrinology, 2023)
This study was designed to investigate the effect of running exercise on improving bone health in aging mice and explore the role of the SIRT1 in regulating autophagy and osteogenic differentiation of Bone Mesenchymal Stem Cells (BMSCs). Twelve-month-old male C57BL/6J mice were used in this study as the aging model and were assigned to treadmill running exercise for eight weeks. Non-exercise same old male C57BL/6J mice were used as aging control and five-month-old mice were used as young controls. The results showed that aging mice had lower bone mass, bone mineral density (BMD), and autophagy than young mice, while running exercise improved BMD and bone mass as well as upregulated autophagy in bone cells. BMSCs were isolated and subjected to mechanical stretching stimulation in vitro. Mechanical loading increased osteogenic differentiation and autophagy in BMSCs, and knockdown of SIRT1 in BMSCs demonstrated that SIRT1-regulated autophagy involved the mechanical loading activation of osteogenic differentiation. Taken together, this study revealed that exercise improved bone health during aging by activating bone formation, which can be attributed to osteogenic differentiation of BMSCs through the activation of SIRT1-mediated autophagy. The mechanisms underlying this effect may involve mechanical loading.